The Revolution of Engineers. Communist Students at the Universities of the Second Polish Republic and Their Formative Experiences - Bertram, Łukasz (Sensus Historiae, 2021)
This article is to analyse the political experience of men and women studying at universities of the Second Polish Republic in the 1930s and at the same time participating in the Polish communist movement in the ranks of the academic organization “Życie.” The paper shows how the biographical experiences of “życiowcy” form a special type of communist biography, and also presents the similarities and differences between it and the most stereotypical model of a communist, i.e. a “professional revolutionary.” Among the issues addressed are the paths of leftist radicalization, a tension between the intellectual nature of the “Życie” milieu and the distrust of the Communist Party of Poland towards the stratum of intelligentsia, prison experience, patterns of distancing oneself from the communist movement, and — in some cases — the paradoxical time of personal prosperity in the period of great purges in the USSR, traumatic for communists. At the same time, the article presents “życiowcy” in relation to their social environment, showing how many elements of their political radicalism they shared with representatives of other political movements and how deeply they were rooted in the experience of young Polish intelligentsia of the time.